Evaluation of bowel peristalsis by dynamic cine MRI: detection of relevant functional disturbances - initial experience - Heye, Tobias; Stein, Daniel; Antolovič, Dalibor; Dueck, Margret; Kauczor, Hans-Ulrich; Hosch, Waldemar P. (Journal of magnetic resonance imaging, 2012)
Purpose: To investigate the diagnostic performance of a cine magnetic resonance imaging (MRI) sequence in the visualization and detection of impaired bowel peristalsis. Materials and Methods: In all, 91 consecutive patients (mean age 45 years) were prospectively examined on a 1.5 T system and stratified into a surgery group (n = 22) and a nonsurgery group (n = 69). A coronal fast imaging with steady-state precession (TrueFISP) sequence with 30 acquisitions per slice covered the abdomen in 10-15 slices each 7-12 mm thick (temporal resolution: 6-8 sec per frame). Image evaluation for reduced bowel peristalsis and relevant bowel stenosis was compared to surgical findings or clinical follow-up. Results: Cine MRI reached 96% accuracy (94% sensitivity; 100% specificity) in detecting a relevant reduction in bowel peristalsis and 85% of relevant stenosis was identified in the surgery group. Twenty of 69 patients of the nonsurgery group showed reduced peristalsis on cine MR which was attributed to underlying disease; 49/69 patients in this group had no findings on cine MR and were uneventfully followed up. Conclusion: Cine MRI of the bowel provides functional information of bowel passage. The visualization of a reduction in peristalsis may improve the assessment of the functional impact of suspected bowel adhesions or stenosis. Standard bowel MR protocols can be easily complemented by cine MR, extending scan time by <4 minutes.